2015
DOI: 10.1055/s-0034-1391323
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for treatment of refractory gastric antral vascular ectasia (with video)

Abstract: Background and study aims: Gastric antral vascular ectasia (GAVE) is a known cause of gastrointestinal bleeding and chronic iron deficiency anemia. Endoscopic therapy with argon plasma coagulation (APC) is widely used for treatment of GAVE, but most patients continue to require repeated blood transfusions and multiple endoscopic procedures (refractory GAVE). We describe our initial experience regarding safety and efficacy of radiofrequency ablation (RFA) therapy in treating patients with refractory GAVE. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…21 In addition, endoscopic RFA required fewer treatment sessions for clinical or endoscopic resolution as compared with APC (a difference of 1.27 endoscopies per successfully treated patient) ( Table 2). [16][17][18][19][21][22][23] Furthermore, both APC and RFA achieved similar increases in mean hemoglobin level; the number of complications also was similar across the 2 modalities. Although only a limited number of studies have been performed to evaluate RFA for the treatment of GAVE (6 RFA studies were included in this meta-analysis), likely in part owing to the novelty of the procedure for this pathology, available evidence suggests that RFA may possess a better efficacy and tolerability compared with APC.…”
Section: Gastric Antral Vascular Ectasiamentioning
confidence: 69%
See 1 more Smart Citation
“…21 In addition, endoscopic RFA required fewer treatment sessions for clinical or endoscopic resolution as compared with APC (a difference of 1.27 endoscopies per successfully treated patient) ( Table 2). [16][17][18][19][21][22][23] Furthermore, both APC and RFA achieved similar increases in mean hemoglobin level; the number of complications also was similar across the 2 modalities. Although only a limited number of studies have been performed to evaluate RFA for the treatment of GAVE (6 RFA studies were included in this meta-analysis), likely in part owing to the novelty of the procedure for this pathology, available evidence suggests that RFA may possess a better efficacy and tolerability compared with APC.…”
Section: Gastric Antral Vascular Ectasiamentioning
confidence: 69%
“…In this study of 24 patients, 23 of whom were transfusion-dependent, the mean number of red cell units transfused decreased in all transfusiondependent patients (mean, 10.6 AE 12.1 before RFA compared with 2.5 AE 5.9 at 6 mo after RFA; P < .001). A more recent case series of 7 patients by Jana et al 19 found endoscopic RFA to be an effective alternative to APC for the treatment of GAVE in patients refractory to previous endoscopic therapy. Although a limited number of patients were enrolled and a median number of 2 RFA sessions produced a modest improvement in hemoglobin level after the procedure, 71% of patients (5 of 7) were no longer transfusion-dependent, with no immediate complications reported.…”
Section: Gastric Antral Vascular Ectasiamentioning
confidence: 99%
“…The first study, conducted on 7 patients treated with the HALO ULTRA system, showed technical and clinical effectiveness in all patients with a mean gain of hemoglobin from 9.3 to 10.1 g/dL during a median follow-up of 6 months, in the absence of adverse events [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic therapies have rapidly become the mainstays of first line therapy namely with argon plasma coagulation (APC) as the most common modality and more recently with radiofrequency ablation (RFA) using Halo 90 catheter[ 9 ] and endoscopic band ligation (EBL) both of which have been shown to be safe and effective for GAVE treatment[ 10 , 11 ]. The latter two have been utilized in treatment of severe, diffuse, APC refractory GAVE[ 10 , 21 ]. Furthermore, there has been the advent of BARR χ Through The Scope technique (Covidien, TTS-1100) for RFA, which posits some advantages over the traditional Halo 90 system.…”
Section: Introductionmentioning
confidence: 99%